An Anthropocentric Approach to The Linguistic Essence of The Term in Uzbek Linguistics - Ikromjon Toshpulatovich Khabibjonov (International Journal Of Literature And Languages, 2025)
Every language has its own unique grammatical structure, which serves as a medium for conveying specific meanings and essences. These elements are closely related to the linguistic, scientific, and spiritual worldview of the speakers of that language. This article briefly discusses the anthropocentric approach to the linguistic essence of the term in Uzbek linguistics.